Evaluation of milk production and milk composition at different stages of Saanen Dairy Goats - Noor Syaheera Ibrahim (2023)
Milk is an important elements due to its high nutritious and balanced in human diet. In Asian, goat milk is the most consumed because of the unique taste, more nutritious than cow milk. However, milk production and composition values differ at every stage of lactation in goats. Thus, determining the highest milk production and producing the best quality goat milk is essential to satisfy the local market demands. The objective of the present study is to determine the milk yield and milk composition at different lactation stages and to evaluate the lactation curves in Saanen goats. The lactation stages can be categorized into three, early (less than 80 days), mid (80 –140 days) and late (over 140 days) days in milk(DIM). In total, 90 milk samples were collected from 15 goats representing early (n=5), mid (n=5), and late (n=5) stages of lactation. The Saanen goats were raised under the same conditions, and milking was done early in the morning (9.00 am). The milk yield from Saanen goats were collected and measured weekly at each stage of lactation. Milk samples were analyzed for fat, protein, solid non-fat, and lactose. Current result illustrated, there were significant different(p ˂0.05) among three stages of lactation in milk yield, solid non-fat, fat, protein and lactose. In terms of food regulation, the Saanen goats almost fully met the standard requirements for milk production and composition. In addition, this study also observes the lactation curves in Saanen goats and analyse the curve shapes and patterns. The average milk yields from three different stages develops a concave downward curve. The results indicated that mid yield increased from early to mid-lactation and decreased there after until the end of lactation.